Balanced energy routing protocol for clustered wireless sensor network. (2017) - Tripathi, Meenakshi; Gaur, M.S.; Laxmi, Vijay; Battula, R.B.
Wireless sensor networks are used to sense the information from the physical world and transfer it to the central location, where the sensed data is being analysed. These sensor nodes are battery operated and it is difficult to recharge them in the field, so inclusion of energy efficiency is must in the protocols of these networks. Clustering is one of the most popular methods to achieve it. In clustering, the network is divided into various clusters and cluster head of every cluster is responsible to transfer the data to central location (base station). This paper introduces a balanced energy routing protocol based on LEACH-C for WSN. Our proposal not only selects the maximum energy node as cluster head but also distributes the load among the various clusters evenly. This balances the energy consumption among various nodes hence increases the lifetime of the network. The performance evaluation of the proposed protocol through simulation indicates a significant improvement in terms of energy efficiency as compared to other well-known protocols.